The Use of Online Media in Learning English During the Pandemic of Covid-19: Study From Home - Siti Munawaro; Maryanti Sawitri; Daris Daris; Pahmi Pahmi; Adang Ridwan (P3M IAI Nusantara Batang Hari, 2022)
The aim of this study was to show student’s competence in using online Media as a tool in English Language learning. Qualitative data were collected from the students of the English Department, Faculty of Education, IAI Nusantara Batanghari. Sample of this study was selected by using purposive sampling. The data collection technique was in the form of interview and observation on learning activity. Then, the data were analyzed descriptively. The result showed that three types of online media utilized by the students such as Zoom application, Video performance and WhatsApp messenger. The most favorite media was WhatsApp messenger due to easy to use, practical, fast use, saving internet data, and can be accessed only with mobile phones. WhatsApp has various features that can be used to support communication such as New Groups, New Broadcasts, WhatsApp Web, Broadcast Messages and Settings with internet service assistance. The group menu option was used as a place for discussion activity for the teacher with students and students with their friends in solving problems, for example the teacher sends several questions to be solved according to the material that has been given.